Identification of Chromosomal Aberrations by Using Trypsin G-banding in Hepatocellular Carcinoma Patients (HCC) in Tamil Nadu, India - Subramaniam Mohana Devi; Vellingiri Balachandar; Palanivel Vel Murugan; Keshavarao Sasikala; Pappusamy Manikantan; Leela Krishnan Venkatakrishnan (Tropical Life Sciences Research, 2010)
Hepatocellular carcinoma (HCC) (or liver cancer) is one of the most common human malignancies worldwide. Aetiologically, HCC is closely associated with chronic hepatitis B and C virus infection, cirrhosis and alcohol intake. The objective of the present study was to elucidate the chromosomal abberations (CA) in HCC patients using the trypsin G-banding technique. This study may help in understanding the pattern of the disease and to assess whether these aberrations are associated with HCC susceptibility. The study examined 51 HCC cases and an equal number (n = 51) of age and gender matched cancer-free controls recruited from the hospitals in Tamil Nadu. The HCC cases were grouped depending upon their age into group I (? 45 years) and group II (? 46 years). The development of effective markers for the detection of HCC could have an impact on cancer mortality and may have significant public health implications worldwide. Subjects were recruited based on their alpha-fetoprotein (AFP) serum level, which is an effective marker for HCC. In the HCC cases, a higher number of chromatid aberrations [group I 13(25.5%) and group II 43(84.3%)] and CA [group I 10(19.6%) and group II 28(54.9%)] were observed. In contrast, controls showed a lower number of chromatid [group I 5(9.8%) and group II 12(23.5%)] and CA [group I 4(7.8%) and group II 9(17.6%)]. In conclusion, the results of this study contribute to the validation of CA as an intermediate end point in carcinogenesis. Because many people are unaware of this lethal disease, this study will raise awareness of this cancer. Hepatocellular carcinoma (HCC) (ataupun kanser hati) merupakan satu daripada malignasi manusia yang paling biasa dilaporkan di dunia. Secara etiologi, HCC berhubung kait dengan jangkitan penyakit kronik hepatitis B dan C, cirrhosis dan pengambilan alkohol. Objektif kajian ini ialah untuk menjelaskan perubahan kromosom (CA) dalam pesakit HCC menggunakan teknik trypsin G-banding. Kajian ini mungkin boleh membantu dalam pemahaman corak penyakit ini, dan untuk menilai jika perubahan kromosom ini terlibat dalam daya rentan HCC. Kajian ini telah memeriksa 51 kes HCC, dan 51 kes kawalan bebas kanser yang sama dari segi umur dan jantina, yang direkrut dari hospitalhospital di Tamil Nadu. Kes-kes HCC telah dikumpulkan mengikut umur iaitu kumpulan I (? 45 tahun) dan kumpulan II (? 46 tahun). Penghasilan penanda yang efektif untuk pengesanan HCC boleh memberi impak terhadap kesihatan awam di seluruh dunia. Subjek-subjek telah direkrut berpandukan aras serum alpha-fetoprotein (AFP), yang merupakan penanda efektif untuk HCC. Nombor perubahan kromatid [kumpulan I 13(25%) dan kumpulan II 43(84.3%)] dan CA [kumpulan I 10(19.6%) dan kumpulan II 28(54.9%)] yang lebih tinggi telah diperhatikan. Bagi kumpulan kawalan, keputusannya kontras, iaitu nombor perubahan kromatid [kumpulan I 5(9.8%) dan kumpulan II 12(23.5%)] dan CA [kumpulan I 4(7.8%) dan kumpulan II 9(17.6%)] ialah lebih kurang. Secara kesimpulannya, keputusan daripada kajian ini telah menyumbang terhadap pengesahan CA sebagai titik akhir pertengahan karsinogenesis. Disebabkan ramai orang tidak sedar tentang penyakit berbahaya ini, kajian ini akan membantu meningkatkan tahap kesedaran tentang kanser ini.